Uncontrolled measles in the age of controlled infections - L.A. Volyanska; E.I. Burbela; L.B. Romanyuk (Zaslavsky O.Yu., 2019)
Background. In the last decade, the incidence of measles has a number of features. The infection migrates from country to country, from continent to continent within a year - a year and a half, despite the state of collective immunity in the territory of its spread. The age priority has disappeared, this infection has lost the status of pediatric, all age categories are affected, with a shift to 14-25 year olds. The purpose was to analyze the causes of insufficient control of the epidemiological process of measles in the Ternopil region in the context of situation in Ukraine. Materials and methods. The materials of the reporting documentation of the Main Epidemiological Service and the children's infectious diseases hospitals of the Ternopil region were used. Results. In the region, some differences in the incidence of measles were observed. In general, they are a reflection of the nationwide problem of managing this infection. The amount of measles, which was recorded in the Ternopil region in 2001, exceeded the general Ukrainian indexes by almost 6 times, which was overcome by active vaccination already in the next peak 2005-2019, and bring the incidence to the republican levels. The regional peak incidence rates were at least 1 year ahead of the national ones, which indicates that this infection was imported into our region across the western border, since there is a coincidence with European data. Epidemic situation of measles in 2000-2019 has a clear dependence on the timeliness and completeness of vaccination coverage by age, state of population immunity. During 2011-2019, 10-18 year olds (65.27 %) with a positive vaccine history dominated in the statistics of measles cases in Ternopil. Among measles patients, the number of people vaccinated is increasing, especially among the age group of 10-18 years. The number of measles among infants is increasing due to the lack of immunity (post-vaccination or post-infectious) in Ukrainian mothers. The incidence rate is determined by the completeness of the coverage of the children's population with calendar vaccinations. Incidence peak shifted to the period of 14-25 years makes it necessary to conduct regular revaccination against measles in this age.